Al-Isyârât al-Kauniyyah fi al-Hurûf al-Muqatha’ah Awâili al-Suwar ‘Inda Thanthawi Jauhari - Ilham Habibullah; Indri Wesdiarti Anggraini (Universitas Darussalam Gontor, 2017)
The scholars differ on the meaning and interpretation of the letters of Muqatha'ah in the Qur'an. This issue also received special attention from the orientalists, because they saw that the letters of Muqatha'ah belong to the deficiency of the Qur'an. According to Thanthawi Jauhari the difference of the scholars includes three things: first, that the letters need not be interpreted because the real meaning is only Allah knows (Mutasyâbihât), secondly, the letters have meaning related to Asma Allah Swt or related to the names of the ' The name of the letter in the Qur'an, third, that the letters are codes containing messages to read the greatness of Allah swt in this universe. That is why according to Thanthawi that